Crack Behavior of Eccentrically Braced Frame Type-V with Ground Granulated Blast Furnace Slag - Yohanes Ola Sira Lamawato; Susanti, Lilya; Wijaya, Ming Narto (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
To make the structure stronger and stiffer, which is more susceptible to earthquake forces, a special mechanism is required to improve the structure's lateral stability. EBF-V with a horizontal link beam is a brace that can enhance structural performance by providing good stiffness and ductility. On the other hand, GGBFS, as a partial OPC replacement material, was applied to contribute to using more environmentally friendly materials. Besides offering a smaller carbon footprint, GGBFS also positively improves the mechanical properties of concrete. Thus, this study focuses on investigating the crack propagation pattern of reinforced concrete braced frames combined with 20% GGBFS in EBF-V with three variations of link beam element lengths of 0 cm (CBF), 15 cm (EBF-V-) and 25 cm (EBF-V-25). As a result, the CBF specimen showed the best seismic performance. In EBF specimens, there is an increase in the collapse mechanism to be more ductile. The link beam plays a role in making the crack pattern more focused. EBF-V-15 performs well under seismic loading with large lateral capacity and ductility. The cracks in the frame are evenly distributed, dominated by fine cracks, and symmetrical on both sides. This validates that GGBFS plays a good role in improving the frame performance with its pore-filling effect and pozzolanic reaction.